Mineralogical Investigation of the Bara Formation from Lakhra Anticline, Sindh province, Pakistan - Asgher Ali Daahar Hakro,; Adnan Khan ,; Sadaf Naseem, (Journal of Basic & Applied Sciences, 2016)
The present study shows the bulk mineralogical composition of the Bara Formation from Lakhra anticline, near to Lakhra coalfield area of the Sindh province of Pakistan. The petrography, scanning electron microscope and X-ray diffractommeter were used for the detailed mineralogical investigations. Quartz, feldspars, hematite, gypsum, chlorite and goethite minerals were obtained from above methods. Quartz, feldspar and chlorite minerals indicated that the sediments were transported from igneous and metamorphic rocks and the hematite and goethite indicated the continental environment for the studied formation. Mineralogical investigation of the Bara Formation indicates that the sediments were supplied from the Igneous and metamorphic rock terrane. It can be said that the Bara formation sediments were supplied from the Igneous and metamorphic complex which is exposed in the southeastern part of the studied area.